CIRCULAR ECONOMY : THE SETTLEMENT OF ENVIRONMENTAL ETHICS PROBLEMS AND THE FUTURE OF NATIONAL ECONOMY - ILHAMSYAH; HARKIM (CV KULTURA DIGITAL MEDIA, 2021)
The purpose of this paper is to explain the possible application of a circular economy model in Indonesia. Circular economy is closely related to environmental ethical problems, especially waste, as a result of the post-use benefit of an item. This paper is a qualitative reflective study with a literature study approach. Reflection is carried out in-depth with literature sources that are compatible and relevant to the study conducted. Thus, the data used are secondary data from credible sources that have been tracked by researchers. Secondary data are analyzed by interacting propositions, textual realities, and other statements considered important by the researcher. The results of the study describe how a circular economy is an actual, moderate alternative to environmental economic and ethical issues. The predicted linear economic limitations do not guarantee balance and environmental sustainability has obtained a replacement model. Thus the circular economy is a potential model for the future of the national economy that needs to be developed.